First Report of the Coexistence of Langerhans Cell Histiocytosis and Epithelioid Hemangioma of the Larynx - Salih Cengiz Meral; Levent Yücel; Egemen Akıncıoğlu; Ömer Günhan; Yavuz Fuat Yılmaz (Turkish Archives of Otorhinolaryngology)
Langerhans cell histiocytosis (LCH) is a complex disorder of the mononuclear phagocyte system. Laryngeal epithelioid hemangiomas are rare, benign vascular tumors in adults. Here, we report the first known case of the coexistence of LCH and epithelioid hemangioma in the larynx. A 42-year-old man presented with progressive swelling on the left side of the neck and hoarseness. Endoscopic examination revealed a mass obliterating the left pyriform sinus, false vocal cord, and aryepiglottic fold. Computed tomography (CT) showed a mass destroying the thyroid cartilage, extending to the left false and true vocal cords, and obstructing the airway. Fine-needle aspiration biopsy suggested hemangioendothelioma. However, histopathological examination after total laryngectomy revealed both LCH and epithelioid hemangioma. Positron emission tomography/CT indicated suspected LCH involvement of the pituitary gland and cervical lymph nodes. The patient was treated with chemotherapy. No recurrence was observed at the six-month follow-up. This case highlights the potential association between the mitogen-activated protein kinase pathway, LCH, and epithelioid hemangioma. It also emphasizes the importance of repeating a biopsy in cases of rare laryngeal tumors when initial results are inconclusive.